Cohesion and Coherence of Students Recount Texts in Indonesia - Priyatmojo, Arif Suryo (Language Circle: Journal of Language and Literature, 2021)
This study aimed at analyzing the cohesion and coherence of recount texts and their implication to teaching writing. The data was fifteen recount texts which were non-randomly chosen from the first-grade students of high school in Central Java, Indonesia. This was qualitative research employing cohesion theory by Halliday and Hasan (1976) and thematic progression proposed by Butt et al. (1995). The result of this research showed that most of the cohesive devices employed by the students were personal reference with 58.11%; demonstrative reference and definite article with 7.18%; comparative reference with 0.93%), lexical (repetition 22.21%; synonym 0.66%; superordinate 0.13%), conjunction (temporal conjunction 7.45%; adversative conjunction: 1.33%; additive conjunction 1.06%; causal conjunction 0.66%), and ellipsis with 2%. The presuppositions of the presupposed items and presupposing items were achieved anaphorically and cataphorically; most of them were anaphoric. The distances of the presuppositions were in the forms of immediate ties, mediated ties, and non-mediated ties. Furthermore, immediate ties occurred extensively. Based on the analysis, most of the texts were cohesive due to the achievement of presupposing and presupposed items in every sentence of the texts. Then, coherence of the students recount texts was achieved by employing three kinds of patterns: reiteration/ constant, zig-zag, and multiple thematic progression patterns. Most of the texts were developed by using a reiteration/ constant pattern. Based on the analysis, most texts were not coherent because of the unrelated clauses. As the result, they broke the signposted progression of the texts. The finding was expected to possibly contribute to the process of teaching writing by encouraging the students to create a good text in a cohesive and coherent way.